A Survey of Alien Dendroflora of Bosnia and Herzegovina - Neđad Bašić; Fatima Pustahija; Aldin Boškailo; Edina Muratović (South-East European Forestry)
The accessible literature sources do not give an integrated register of non-native tree species in Bosnia and Herzegovina and western Balkans floras. Therefore, the focus of this study was on an inventory of allochthonous dendroflora in the territory of Bosnia and Herzegovina (B&H) by 2023. Numerous literature sources, the herbarium collection of the National Museum of Bosnia and Herzegovina (SARA) and the authors' field investigations were used to create the allochthonous B&H dendroflora list. The inventory list comprises dendro species of trees, shrubs and lianas. The survey consists of 552 non-native dendro taxa, associated with family, geographic origin, residence time status, degree of naturalization, zone of resistance, and abundance of the investigated taxa. A total of 82 families, 208 genera, and 552 taxa, which included species level, subspecies, varieties, and hybrids were recorded. The B&H allochthonous dendroflora generally originate from Asia (260 taxa) and North America (128), with a significant share of hybrids (81). Only 19 archaeophytes were registered. According to the degree of naturalization, it was observed that as many as 451 taxa are casual and 13 invasive. The non-native dendro species in B&H mainly belong to the USDA Hardiness Zones 4-9, 5-9 and 6-9. The alien dendroflora of B&H includes 152 occasional, 142 rare, 198 abundant and only 60 taxa with massive abundance. The presented results give a detailed insight into the allochthonous dendroflora of B&H, which is also the first such presentation for the Western Balkans.